Design of PID Disturbance Observer for Temperature Control on Room Heating System - Yoga Alif Kurnia Utama; Yulius Hari (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Heat is one of an energy form that can move from a high temperature to a low temperature. This will strongly make the temperature outside of the room affect the temperature in the room. Therefore, the temperature in the room becomes unstable. That is a problem for room heating system which requires a stable indoor temperature output. Because of that reason, so the system needs temperature control method that can reject disturbance that derived from the outdoor temperature. This research will propose a solution that is the use of PID Disturbance Observer (PID-DOB) method for resolving that problem. The tests that we carried out is comparing the PID controller and PID-DOB by simulation with four variation temperature and calculating the performance index by using integral time absolute error (ITAE) criteria. The result showed that the ITAE average for PID is 10.51 and PID-DOB are 1.78. This result showed that PID-DOB controller can be used as temperature control which resists to the varied temperature outside the room.